Teachers’ Knowledge Regarding First Aids: A Cross-Sectional Study: Pengetahuan Guru Mengenai Pertolongan Pertama: Sebuah Studi Cross-Sectional - Wathiq Faraon Hussein (Academia Open, 2024)
Background: In the Chain of Survival, proficiency in first aid is crucial, especially in large gatherings like schools where emergency health crises are more likely. Objective: This study's principal goals were to investigate primary school teachers' first aid knowledge and identify any correlations between their level of knowledge and the study's factors. Methods: In Basrah City, ten primary schools took part in a descriptive cross-sectional survey. This study was carried out between September 1, 2021, and the end of April 2022 in order to assess the teacher's first aid expertise. A chance (random) sample of 161 male and female educators from the ten schools was selected for the study. A closed-ended questionnaire was used to collect data. There are three portions to the survey. Six questions on the teachers' sociodemographic characteristics are asked in the first segment, and twelve questions concerning their acquaintance with the school's ambulance and first aid equipment are asked in the second section. The final component of the questionnaire asks 26 questions about the teachers' first aid knowledge. The data was analyzed using SPSS (Statistical Package for Social Sciences) version 20. Results: 10.6% are chemists, 26.1% are biologists, 14.9% have physical training, 19.3% are social scientists, 13% are English speakers, 16.1% speak Arabic, and 19.3% are social scientists. 51.4% had been employed for 5–10 years, 35.4% for 11–25 years, and 11.2% for over 26 years. Conclusion: revealed how well-informed the teachers were on first aid cabinets and ambulances, as evidenced by the fact that the mean scores for all items were more than 2. Highlights: Teachers' first aid knowledge is crucial in emergency situations.Cross-sectional survey of 161 teachers using questionnaires.Teachers demonstrated moderate knowledge of first aid and equipment. Keywords: Teachers, Knowledge, First Aids